Ants and the origins of plant diversity in old, climatically stable landscapes: A great role for tiny players - Mucina, Ladislav; Majer, Jonathan (Elsevier, 2012)
The exceptionally high plant diversity in the Cape region of southern Africa continues to attract considerable attention. In a recent paper Linder et al. (2010) concluded that diversification has been promoted by the physical complexity of the Cape environment and by certain biotic interactions, such as those between bees and flowering plants. Although these authors acknowledge the potential role of seed dispersal by ants, they suggested that there were no tests which would demonstrate whether rates of diversification were higher in myrmecochorous lineages versus those with other biotic or abiotic dispersal mechanisms. Here we argue that a set of recent papers by Dunn et al. (2007) and Lengyel et al. (2009, 2010) provide compelling evidence that myrmecochory may have resulted in a doubling of plant diversification, largely due to the greater likelihood of genetic isolation and also of the increased survival rate of plants possessing this dispersal mode. Here, we suggest that myrmecochory, which may be favoured in low nutrient soils, could be a key contributor to the high floristic biodiversity in the Cape region, as well as in other old, climatically stable landscapes such as those of southwest Australia.